Reimagining Higher Education in Nepal: Challenges and Opportunities - Dahal , Nirod Chandra; Baral , Yamnath (Educational Journal, 2024)
Nepal’s higher education system faces persistent structural and systemic barriers such as inadequate governance, limited research capacity, inequities in access, and misalignment with labour market demands-despite recent reform efforts and growing enrolment. This study aims to evaluate current reforms and identify strategic interventions that can enhance quality, equity, and relevance in Nepal’s higher education sector. Employing qualitative policy analysis, the research integrates a critical review of national educational policy documents, scholarly literature, and comparative global trends. The findings indicate that initiatives including digitalisation, decentralisation, and expansion of technical and vocational education have been initiated but remain disjointed and inconsistently implemented. Key reform needs identified are strengthening institutional autonomy and quality assurance systems, aligning academic curricula with market needs, fostering research and innovation culture, and leveraging digital technologies to modernise teaching and governance. The study concludes with evidence-based policy recommendations designed to guide Nepal’s transition to an inclusive, competency-based, future-ready higher education model.